2007
DOI: 10.1002/jmr.835
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent localization of GPI‐anchored intestinal alkaline phosphatase in model rafts

Abstract: In plasma membranes, most of glycosylphosphatidylinositol (GPI)-anchored proteins would be associated with rafts, a category of ordered microdomains enriched in sphingolipids and cholesterol (Ch). They would be also concentrated in the detergent resistant membranes (DRMs), a plasma membrane fraction extracted at low temperature. Preferential localization of GPI-anchored proteins in these membrane domains is essentially governed by their high lipid order, as compared to their environment. Changes in the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…This finding lent strong support to our earlier suggestions that PM is involved in the sensing of temperature elevations through changes in the physical state of the membrane [36,42,43]. Interestingly, in artificial bilayer systems, atomic force microscopy studies have shown that GPI-anchored proteins can be released from the liquid ordered phase by an increase in temperature [44]. Thus, a similar mechanism may apparently account for the observed dissociation of mGFP-GPI homo-associates in the CHO cell membrane.…”
Section: Membranes Are Key Determinants Of Cellular Stress Adaptationsupporting
confidence: 87%
“…This finding lent strong support to our earlier suggestions that PM is involved in the sensing of temperature elevations through changes in the physical state of the membrane [36,42,43]. Interestingly, in artificial bilayer systems, atomic force microscopy studies have shown that GPI-anchored proteins can be released from the liquid ordered phase by an increase in temperature [44]. Thus, a similar mechanism may apparently account for the observed dissociation of mGFP-GPI homo-associates in the CHO cell membrane.…”
Section: Membranes Are Key Determinants Of Cellular Stress Adaptationsupporting
confidence: 87%
“…It is thus attractive to speculate that the plasma membrane may be involved in sensing small temperature elevations. Interestingly, in artificial bilayer systems, atomic force microscopy studies have shown that GPI-anchored proteins can be released from the liquid-ordered phase by an increase in temperature (44); a similar mechanism may account for the observed dissociation of mGFP-GPI homo-associates in the CHO cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the insertion and the redistribution of the lipids it is probable that GPI-anchored proteins, once in the lipid bilayer, recruit the most suitable lipid environment most likely by exploiting the hydrophobic matching interaction. The AFM can also be exploited to observe the redistribution of GPI-anchored proteins after a temperature variation (Giocondi et al, 2007b). The obtained information can be fruitfully compared with results obtained from DRM extraction at low temperature.…”
Section: Chapter 2: Lipid/protein Interaction Studied By Afmmentioning
confidence: 99%